(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2023)
This study aimed to systematize and evaluate the effects of a brief intervention (Conecta) focused on promoting body image flexibility and reducing body image dissatisfaction and risk behaviors for eating disorders (ED). It was also intended to assess the intervention acceptability and feasibility. This is a pre-experimental study, and data was collected at the baseline and at the end of the intervention. Nineteen undergraduate female students aged 18 to 33 years were assigned to the workshop. The brief intervention consisted of three weekly face-to-face meetings. The results revealed a significant increase in levels of body image flexibility, mindfulness, openness to experience and current perception of health, as well as a significant reduction of body image dissatisfaction and risk for developing ED. Our results suggest that a brief workshop may be applicable for female students experiencing distress related to body image.